Factors associated with antimicrobial resistant enterococci in Canadian beef cattle: A scoping review - Strong, Kayla M.; Marasco, Kaitlin L.; Invik, Jesse; Ganshorn, Heather; Reid-Smith, Richard J.; Waldner, Cheryl L.; Otto, Simon J. G.; Kastelic, John P.; Checkley, Sylvia L. (Frontiers in Veterinary Science, 2023)
Introduction: Antimicrobial resistance (AMR) is a global health concern, occurring when bacteria evolve to render antimicrobials no longer effective. Antimicrobials have important roles in beef production; however, the potential to introduce AMR to people through beef products is a concern. This scoping review identifies factors associated with changes in the prevalence of antimicrobial-resistant Enterococcus spp. applicable to the Canadian farm-to-fork beef continuum. Methods: Five databases (MEDLINE, BIOSIS, Web of Science, Embase, CAB Abstracts) were searched for articles published from January 1984 to March 2022, using a priori inclusion criteria. Peer-reviewed articles were included if they met all following criteria: written in English, applicable to the Canadian beef production context, primary research, in vivo research, describing an intervention or exposure and specific to Enterococcus spp. Results: Out of 804 screened articles, 26 were selected for inclusion. The included articles discussed 32 factors potentially associated with AMR in enterococci, with multiple articles discussing at least two of the same factors. Factors discussed included antimicrobial administration (n=15), raised without antimicrobials (n=6), metal supplementation (n= 4), and grass feeding (n=1). Probiotics supplementation (n=3), essential oil supplementation (n=1), feeding wet distiller grains with solubles (n=1), and processing plant type (n=1) were secondary factors investigated in six articles. Results were included irrespective of their quality of evidence. Discussion: Comparability issues arising throughout the review process were related to data aggregation, hierarchical structures, study design, and inconsistent data reporting. Findings from articles were often temporally specific in that resistance was associated with AMR outcomes at sampling times closer to exposure compared to studies that sampled at longer intervals after exposure. Resistance was often nuanced to unique gene and phenotypic resistance patterns that varied with species of enterococci. Intrinsic resistance and interpretation of MICs varied greatly among enterococcal species, highlighting the importance of caution when comparing articles and generalizing findings.